Numerische Simulation von Fluid-Struktur-Interaktionen anRohrbündel-Wärmetauschern mittels kommerzieller Software - Youssef Mehrez (2012)
In this work, we shall consider the flow in clusters of densely packed cylinders called tube bundles and the associated fluid-structure interaction. These arrays of tubes are arranged in in-line (straight) configuration. The transverse (T/D) is 2.25, where T/D is the ratio of horizontal distance between cylinder centers (T) and the cylinder diameter (D). A Reynolds number of 5600 was in this study examined. Beginning with a twodimensional unsteady calculation, the flow pattern using the computational fluid dynamics code CFX and different turbulence models has been investigated. In addition, a threedimensional CFD calculation, was also carried out for comparison. It was noted, that in both Simulations the vortex shedding has a direct effect on parameters such as lift and drag forces. The highest lift coefficients are present on rods of the second and third rows because there arise the highest fluctuation velocities caused by turbulence. Using a modal analysis, the dynamic behavior of the rod was described and resonant frequencies of the oscillation were avoided. Finally, coupled numerical simulations of fluid-structure interaction were successfully carried out and the mutual influence of the flow field on the rod structure could be described. Despite all the difficulties of the CFD computational grid movement, the software ANSYS CFX showed that it is an efficient tool for two-way coupled fluid-structure interaction.